In situ biomonitoring of juvenile Chinook salmon (Onchorhynchus tshawytscha) using biomarkers of chemical exposures and effects in a partially remediated urbanized waterway of the Puget Sound, WA - Browne, Eva (2010)
In situ biomonitoring has been used to assess the effects of pollution on aquatic species in heavily polluted waterways. In the current study, we used in situ biomonitoring in conjunction with molecular biomarker analysis to determine the effects of pollutant exposure in salmon caged in the Duwamish waterway, a Pacific Northwest Superfund site that has been subject to remediation. The Duwamish waterway is an important migratory route for Pacific salmon and has received historic inputs of polycyclic aromatic hydrocarbons (PAHs) and polychlorinated biphenyls (PCBs). Juvenile pre-smolt Chinook salmon (Oncorhynchus tshawytscha) caged for 8 days in the three contaminated sites in close proximity within the Duwamish were analyzed for steady state hepatic mRNA expression of 7 exposure biomarker genes encompassing several gene families and known to be responsive to pollutants, including cytochrome P4501A (CYP1A) and CYP2K1, glutathione S-transferase π class (GST pi), microsomal GST (mGST), glutamylcysteine ligase catalytic subunit (GCLC), UDP-glucuronyltransferase family 1 (UDPGT), and type 2 deiodinase (type 2 DI, or D2). Quantitation of gene expression was accomplished by quantitative reverse transcriptase polymerase chain reaction (qRT-PCR) in assays developed specifically for Chinook salmon genes. Gill PAH-DNA adducts were assessed as a chemical effects biomarker using (32)P-postlabeling. The biomarkers in the field-caged fish were analyzed with respect to caged animals maintained at the hatchery receiving flow-through water. Chemical analysis of sediment samples from three field sampling sites revealed relatively high concentrations of total PAHs in one site (site B2, 6711 ng/g dry weight) and somewhat lower concentrations of PAHs in two adjacent sites (sites B3 and B4, 1482 and 1987 ng/g, respectively). In contrast, waterborne PAHs at all of the sampling sites were relatively low (<1 ng/L). Sediment PCBs at the sites ranged from a low of 421 ng/g at site B3, to 1160 ng/g at site B4, and there were no detectable waterborne PCBs at any of the sites (detection limit=10 ng/L). There were no significant differences (P<0.05) in biomarker gene expression in the Duwamish-caged fish relative to controls, although there was a pattern of gene expression suppression at site B3, the most heavily PAH-enriched site. The lack of a marked perturbation of mRNA biomarkers was consistent with relatively low levels of gill PAH-DNA adduct levels that did not differ among caged reference and field fish, and which were also consistent with relatively low waterborne concentrations of chemicals. The results of our study suggest a low bioavailability of sediment pollutants in caged juvenile Chinook potentially reflecting low waterborne exposures occurring at contaminated sites within the Duwamish waterway that have undergone partial remediation.